2015
DOI: 10.1007/s10530-015-0989-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and predicting the spread of non-native raccoons in Germany using hunting bag data and dispersal weighted models

Abstract: 34As the second largest cause of biodiversity loss worldwide, there is an urgent need to study the dynamics of 35 biological invasions and identify factors limiting the distribution of invasive alien species. In the present study 36 we analyze national-scale hunting bag data from Germany to predict the dispersal of raccoons in the largest non-37 native population of the species. Our focus is (1) to document changes in the distribution and abundance of 38 raccoons, (2) to identify the species-environment relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Müritz National Park (MNP) (53° 27′ N, 12° 49′ E) located in Mecklenburg-Vorpommern contains a large amount of wetland habitats, especially bog and swamp districts. This area demonstrates a very opportune habitat for raccoon—its population density in the area is twice as much as that in the middle part of Germany (6–8 individuals per 1 km 2 ) (Fischer et al 2016; Hohmann 1998; Köhnemann and Michler 2008; Muschik et al 2011).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Müritz National Park (MNP) (53° 27′ N, 12° 49′ E) located in Mecklenburg-Vorpommern contains a large amount of wetland habitats, especially bog and swamp districts. This area demonstrates a very opportune habitat for raccoon—its population density in the area is twice as much as that in the middle part of Germany (6–8 individuals per 1 km 2 ) (Fischer et al 2016; Hohmann 1998; Köhnemann and Michler 2008; Muschik et al 2011).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, studies involving native or established occurrences of raccoon are not comparable to those from newly invaded areas. Previous invasive species distribution models (iSDMs) in the core area of the European raccoon population [41] and at the southern border of its current distribution range [42] revealed that either land-cover data or climate data explained raccoon distribution. Furthermore, the habitat preferences of alien species can spatially vary across landscapes and depend on the stage of colonization, with less favorable habitats only being occupied when comparably high population densities are reached [41,43].…”
Section: Introductionmentioning
confidence: 99%
“…Previous invasive species distribution models (iSDMs) in the core area of the European raccoon population [41] and at the southern border of its current distribution range [42] revealed that either land-cover data or climate data explained raccoon distribution. Furthermore, the habitat preferences of alien species can spatially vary across landscapes and depend on the stage of colonization, with less favorable habitats only being occupied when comparably high population densities are reached [41,43]. Studies of other invasive species have provided indications that including distribution data both from native and invasive ranges might yield better iSDMs than models relying solely on data from native ranges [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such harvesting inventories may extend continuously over several decades, and thus describe an abundant source of information for many game species. Although they may have a multitude of limitations, systematically aggregated and wellreplicated hunting/harvesting records can provide a particularly useful supplement for the estimation of large vertebrate spatial distribution dynamics (Fischer et al 2016).…”
Section: Introductionmentioning
confidence: 99%